Synaptic Components, Function and Modulation Characterized by GCaMP6f Ca2+ Imaging in Mouse Cholinergic Myenteric Ganglion Neurons - Margiotta, Joseph F.; Smith-Edwards, Kristen M.; Nestor-Kalinoski, Andrea; Davis, Brian M.; Albers, Kathryn M.; Howard, Marthe J. (Frontiers in Physiology, 2021)
The peristaltic contraction and relaxation of intestinal circular and longitudinal smooth muscles is controlled by synaptic circuit elements that impinge upon phenotypically diverse neurons in the myenteric plexus. While electrophysiological studies have provided useful information concerning the properties of such synaptic circuits, they involve tissue disruption and do not correlate circuit activity with biochemically defined neuronal phenotypes. To overcome these limitations, mice were engineered to express the sensitive, fast Ca2+ indicator GCaMP6f selectively in neurons that express the acetylcholine (ACh) biosynthetic enzyme choline acetyltransferse (ChAT) thereby allowing rapid activity-driven changes in Ca2+ fluorescence to be observed without disrupting intrinsic inputs, solely in cholinergic myenteric ganglion (MG) neurons. Experiments with selective receptor agonists and antagonists reveal that most colonic cholinergic (i.e. GCaMP6f+/ChAT+) MG neurons express nicotinic ACh receptors (nAChRs), particularly the ganglionic subtype containing 3 and 4 subunits, and most express ionotropic serotonin receptors (5-HT3Rs). Cholinergic MG neurons also display small, spontaneous Ca2+ transients occurring at ≈ 0.2 Hz. Experiments with inhibitors of Na+ channel dependent impulses, presynaptic Ca2+ channels and postsynaptic receptor function reveal that the Ca2+ transients arise from impulse-driven presynaptic activity and subsequent activation of postsynaptic nAChRs or 5-HT3Rs. Electrical stimulation of axonal connectives to MG evoked Ca2+ responses in the neurons that similarly depended on nAChRs or/and 5-HT3Rs. Responses to single connective shocks had peak amplitudes and rise and decay times that were indistinguishable from the spontaneous Ca2+ transients and the largest fraction had brief synaptic delays consistent with activation by monosynaptic inputs. These results indicate that the spontaneous Ca2+ transients and stimulus evoked Ca2+ responses in MG neurons originate in circuits involving fast chemical synaptic transmission mediated by nAChRs or/and 5-HT3Rs. Experiments with an 7-nAChR agonist and antagonist, and with pituitary adenylate cyclase activating polypeptide (PACAP) reveal that the same synaptic circuits display extensive capacity for presynaptic modulation. Our use of non-invasive GCaMP6f/ChAT Ca2+ imaging in colon segments with intrinsic connections preserved, reveals an abundance of direct and modulatory synaptic influences on cholinergic MG neurons.